Modeling developmental changes in functional capacities and soccer-specific skills in male players aged 11-17 years - Valente-dos-Santos, J.; Coelho e Silva, M. J.; Simoes, F.; Figueiredo, A. J.; Leite, N.; Elferink-Gemser, M. T.; Malina, R. M.; Sherar, L. (Pediatric Exercise Science, 2012)
This study evaluates the contributions of age, growth, skeletal maturation, playing position and training to longitudinal changes in functional and skill performance in male youth soccer. Players were annually followed over 5 years (n = 83, 4.4 measurements per player). Composite scores for functional and skill domains were calculated to provide an overall estimate of performance. Players were also classified by maturity status and playing position at baseline. After testing for multicollinearity, two-level multilevel (longitudinal) regression models were obtained for functional and skill composite scores. The scores improved with age and training. Body mass was an additional predictor in both models [functional (late maturing): 13.48 + 1.05 × centered on chronological age (CA)—0.01 × centered CA2—0.19 × fat mass (FM) + 0.004 × annual volume training—1.04 × dribbling speed; skills (defenders): 7.62 + 0.62 × centered CA—0.06 × centered CA2 + 0.04 × fat-free mass—0.03 x FM + 0.005 × annual volume training—0.19 × repeated-sprint ability + 0.02 × aerobic endurance]. Skeletal maturity status was a significant predictor of functional capacities and playing position of skill performance. Sound accuracy of each multilevel model was demonstrated on an independent cross-sectional sample (n = 52).